Changing Morphology of Graves and Burials in Samoa - Lilomaiava-Doktor, Saʻ˜iliemanu (Waka Kuaka, 2016)
Of the most important ritual events among Samoans, referred to as faʻalavelave, funerals are often the most elaborate. In this article, I examine the factors that influence decisions about graves and the location of grave sites, and the most recent option of cremation, rather than burial, in the context of migration and social change. I also argue that place as identity is intimately bound up with conceptions of kinship that define where the ʻāiga (extended family, kindred) are buried, faʻasinomaga (identity, belonging) and fanua (land).